Segmental congenital hemangiomas: Three cases of a rare entity. Issue 3 (7th April 2020) - Smith, Robert J.; Metry, Denise; Deardorff, Matthew A.; Heller, Elizabeth; Grand, Katheryn L.; Iacobas, Ionela; Rubin, Adam I.; Phung, Thuy L.; Lopez‐Terrada, Dolores; Steicher, Jenna; Cahill, Anne Marie; Low, David; et al.
Abstract: Congenital hemangiomas (CHs) are unusual and diverse tumors distinguished from infantile hemangiomas by being largely developed at birth and glucose transporter (GLUT1)‐negative. We describe three infants who presented in utero or at birth with segmentally distributed vascular tumors that were GLUT1‐negative, had histology compatible with congenital hemangioma, and exhibited spontaneous clinical involution. One of the three patients had high‐output cardiac failure and was found to have a mutation in GNAQ (c.626A>c, p.Gln209Pro); another had high‐output cardiac failure, heterotaxy, and transient hematologic abnormalities and was found to have a mutation in GNA11 (c.626_627delinsCC, p.Gln209Pro). In addition to describing a novel segmental pattern of congenital hemangioma variant with genetic correlations, these cases illustrate the utility of targeted genetic testing to elucidate the exact mutation and thus classification of vascular tumors.